OUTCOMES OF PERCUTANEOUS CORONARY INTERVENTION IN ST ELEVATION MYOCARDIAL INFARCTION AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - O. M. Polikutina; Yu. S. Slepynina; E. D. Bazdyrev; O. L. Barbarash (Российский кардиологический журнал)
Aim. To evaluate the influence of comorbid chronic obstructive pulmonary disease (COPD) on the prognosis of ST elevation myocardial infarction patients (STEMI) underwent percutaneous coronary intervention (PCI) during acute phase.Material and methods. In the study, 529 STEMI patients included, males — 343 (64,8%), hospitalized during 24 hours from MI onset. Group 1 consisted of patients previously diagnosed with COPD — 65 (12,3%), group 2 — non-COPD — 464 (87,7%). PCI was done for 46,2% COPD and 47,8% non-COPD patients.Results. During one year post MI in the group of comorbid COPD, there was more common angina progression, decompensation of CHF and all non-fatal endpoint (p=0,0022). Presence of COPD in PCI patients increased 3,5 times the risk of combination endpoints (95% CI 1,5-8,1; p=0,0031).Conclusion. Patients with cardiopulmonary comorbidity require special control at outpatient stage after myocardial revascularization.